2006
DOI: 10.1080/13607860500310633
|View full text |Cite
|
Sign up to set email alerts
|

Elderly depressed patients: What are their views on treatment options?

Abstract: The aim of this study was to explore attitudes of elderly patients with depression receiving secondary psychiatric care towards different types of treatment for depression. One hundred patients, recruited from a large teaching hospital in Birmingham, were subjected to structured interviews at which their attitudes towards the effectiveness, likelihood of causing side-effects and acceptability of anti-depressant medication, ECT and psychotherapy were measured on a five-point Likert scale. Psychotherapy was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Earlier on we described that strong negative attitudes towards ECT still prevail in the Netherlands among both professionals and elderly patients (van der Wurff et al, 2004). In a recent study in the UK the views of elderly depressed patients concerning ECT were in line with our findings in this respect (Kuruvilla et al, 2006). Although the recruitment procedure employed yield adequate numbers of participating patients in previous trials, a trial with ECT was not feasible as it resulted in only five eligible participants.…”
Section: Discussionsupporting
confidence: 85%
“…Earlier on we described that strong negative attitudes towards ECT still prevail in the Netherlands among both professionals and elderly patients (van der Wurff et al, 2004). In a recent study in the UK the views of elderly depressed patients concerning ECT were in line with our findings in this respect (Kuruvilla et al, 2006). Although the recruitment procedure employed yield adequate numbers of participating patients in previous trials, a trial with ECT was not feasible as it resulted in only five eligible participants.…”
Section: Discussionsupporting
confidence: 85%
“…More than half of these studies which had reported low rates of perceived benefi t from ECT were surveys conducted by consumer organizations (Rogers and Pilgrim 1993;United Kingdom Advocacy Network 1995;Mental Health Foundation 1997;ECT Anonymous 1999;Pedler 2000;Manic Depression Fellowship 2002;Philpot et al 2004) These consumer surveys also found that dissatisfaction with ECT was more widespread than is often supposed, with up to 50% of the patients expressing negative attitudes regarding ECT. A high prevalence of negative views on ECT among patients (34-75%), was also found in three studies conducted by clinicians (Kuruvilla et al 2006;Arshad et al 2007;Bustin et al 2008). Finally, qualitative data from several studies and accounts of patients also revealed that negative attitudes regarding ECT were quite common (Johnstone, 1999;Froede and Baldwin 1999;Philpot et al, 2004;Rose et al 2004).…”
Section: Other Methodological Considerationsmentioning
confidence: 59%
“…Many researchers from India had explored the knowledge and views of patients and their relatives toward ECT and found that the knowledge and acceptance of ECT were poor. [26][27][28] The pre-assessment knowledge scores of the present study indicated that many subjects were unaware of the ECT procedure and the related facts. The fear of anesthesia, brain damage, and memory loss and the stigma associated with the treatment were reported by other researchers as the main issues raised by the patients and caregivers.…”
Section: Discussionmentioning
confidence: 99%